Effects of Panax notoginseng saponins on receptor-operated Ca2+ channels in vascular smooth muscle - Guan Yong-yuan; Kwan Chiu-yin; He Hua; Sun Jia-jun; Daniel Edwin E (Acta Pharmacologica Sinica, 2016)
The effects of saponins of Panax notoginseng (PNGS) on the alpha-adrenoceptor agonists-induced contractile responses and Ca2+ movement were studied in dog mesenteric artery (MA) and saphenous vein (SV). PNGS reduced the contractions and the 45Ca influx (from 0.36 +/- 0.03 to 0.14 +/- 0.05 mumol.g-1 wet strip) induced by phenylephrine (Phe) without effect on KCl-induced contraction and 45Ca influx which were nearly completely inhibited by nifedipine 0.1 mumol.L-1. PNGS did not change the 45Ca efflux induced by Phe and the Kd value (from 0.76 +/- 0.04 to 0.72 +/- 0.15 nmol.L-1) for [3H]prazosin binding on the microsomal membrane isolated from MA. Our results indicate that PNGS selectively inhibits Ca2+ entry through receptor-operated Ca2+ channel.